Strength distribution at interface of rotary-friction-welded aluminum to nodular cast iron - 宋雨来 刘耀辉 朱先勇 于思荣 张英波 (Transactions of Nonferrous Metals Society of China, 2008)
The morphology, size and composition of intermetallic compound at the interface of AI 1050 and nodular cast iron were studied by electron microprobe analysis（EMPA） and scan electron microscopy （SEM）, respectively. The bond strength of the interface was measured by the tensile tests and the morphology of the fracture surface was observed by SEM. The observation of the interface reveals that there are two distinct morphologies： no interrnetallic compound exists in the central area at the interface; while numbers of intermetallic compounds （FexAly） are formed in the peripheral area due to the overfull heat input. The tensile tests indicate that the distribution of strength in radial direction at the interface is irdaomogeneous, and the central area of the interface performs greater bond strength than the peripheral area, which proves directly that the FexAly intermetallic compounds have a negative effect on the integration of interface. The morphology on the fracture surface shows that the facture in the central area at the interface has characteristic of the ductile micro-void facture. So it is important to restrain the form of the intermetallic compound to increase the bond strength of the AI 1050 and nodular cast iron by optimizing welding parameters and the geometry of components.